2011
DOI: 10.1210/jc.2011-1227
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease Is Associated with Low Circulating Levels of Insulin-Like Growth Factor-I

Abstract: These data show that IGF-I levels are reduced in subjects with NAFLD and suggest that hepatic insulin resistance may affect IGF-I levels by modulating GH-stimulated synthesis of hepatic IGF-I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 20 publications
3
78
0
1
Order By: Relevance
“…Conversely, a smaller study of 55 patients with NAFLD found no association between grade of fibrosis and GH concentrations. Perhaps unsurprisingly, as IGF1 is predominantly produced by the liver, there was a negative correlation between IGF1 and fibrosis stage (58) and low levels of circulating IGF1 in patients with NAFLD has been replicated in other studies (59). Using dynamic tests, peak levels of GH and IGF1 are reduced in patients with NAFLD (60), and in patients with pituitary disease, GH deficiency appears to be associated with increased hepatic lipid content (61).…”
Section: Oestrogensmentioning
confidence: 78%
“…Conversely, a smaller study of 55 patients with NAFLD found no association between grade of fibrosis and GH concentrations. Perhaps unsurprisingly, as IGF1 is predominantly produced by the liver, there was a negative correlation between IGF1 and fibrosis stage (58) and low levels of circulating IGF1 in patients with NAFLD has been replicated in other studies (59). Using dynamic tests, peak levels of GH and IGF1 are reduced in patients with NAFLD (60), and in patients with pituitary disease, GH deficiency appears to be associated with increased hepatic lipid content (61).…”
Section: Oestrogensmentioning
confidence: 78%
“…In addition, a meta-analysis of 42 observational studies demonstrated that elevated circulating IGF1 levels were significantly associated with prostate cancer risk (odds ratio, 1.21; 95% CI, 1.07-1.36) (Rowlands et al 2009). The liver is the main site of circulating IGF1 in humans (Jones & Clemmons 1995), and an increasing body of evidence has suggested that NAFLD is associated with low circulating levels of IGF1 (Arturi et al 2011, Fusco et al 2012. Thus, low circulating levels of IGF1 in NAFLD could explain to some extent why NAFLD is negatively associated with prostate cancer BCR after radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, NAFLD is associated with low circulating levels of IGF-I [65,66]. IL-6 and IGF-I are inde- …”
Section: Discussionmentioning
confidence: 99%